ANALISIS MODEL PEMBAHARUAN HUKUM ISLAM DI INDONESIA MELALUI WASIAT WAJIBAH - Irsan; Aslati Aslati; Khairunnas Jamal (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2023)
ABSTRACT This research aims to analyze the model for reforming Islamic law in Indonesia through mandatory wills. This research is library research. The primary data for this research is the text of the Compilation of Islamic Law Article 209 paragraphs 3 and 4: